Identifikasi Bakteri Indigenous Sebagai Agen Bioremediasi di Lahan Pertanian Cabai Merah Keriting (Capsicum Annum) Yang Terpapar Pestisida Profenofos - Sarah Safira; Kartika Manalu; Rizki Amelia Nasution (Lembaga Pengembangan Kinerja Dosen, 2026)
Indigenous bacteria are microorganisms that naturally live and adapt to specific environments, making them unique to that area. In bioremediation, these bacteria play a crucial role due to their ability to degrade various environmental contaminants, such as the pesticide profenofos left in the soil. This ability makes indigenous bacteria effective and cost-efficient agents in addressing environmental pollution, highlighting their importance in agricultural land recovery research. The aim of this study is to isolate and identify indigenous bacteria from soil exposed to profenofos pesticide and analyze them descriptively. The study is divided into several stages: sample collection, isolation using Nitrate Minerals Salts (NMS) medium, ability testing using Muller Hilton Agar (MHA) medium, characterization, Gram staining, and biochemical testing. The results revealed that 8 isolates have potential as bioremediation agents for soil contaminated with profenofos. In the ability test against the pesticide, the antibacterial inhibition of profenofos was categorized into four levels: weak, moderate, strong, and very strong. The results showed that the isolate with the code BIPC 8 had the highest clear zone diameter of 32.95 mm, indicating a very strong ability. Out of the 8 isolates, 7 were categorized as strong and 1 as very strong, showing potential to reduce profenofos residues in the soil. The identified genera of these isolates include Nitrosoccocus, Bacillus, Pseudomonas, and Rhodococcus. In conclusion, indigenous bacteria are capable of degrading profenofos pesticide.